An analysis of the characteristics of precipitation in the Northeast passage and its relationship with sea ice - Cheng, Maoce; Qiu, Yubao; Yang, Meng; Huang, Lin; Chen, Jianguo; Li, Yang (Frontiers in Environmental Science, 2022)
As an important part of Arctic atmospheric circulation, Arctic precipitation is significant to the energy budget and hydrological characteristics of the Arctic region. The distribution of precipitation has an influence on the energy exchange, which affects the Arctic sea ice indirectly. Arctic precipitation impacts the sea surface albedo and leads to the change of sea ice concentration (SIC) and the energy exchange between sea, ice, and air. The study uses the GPM IMERG precipitation data with 0.1° spatial resolution to discover the precipitation characteristics of the Northeast Passage (NEP) from May to December in each year from 2011 to 2020. The precipitation distribution and magnitude were compared and analyzed in the Barents Sea, the Kara Sea, the Laptev Sea, and the East Siberian Sea. And the study explores the relationship between precipitation and sea ice. The results show that the annual average precipitation is 57-561 mm/year in the Barents Sea and has the largest precipitation in the NEP. The annual average precipitation is 50-386 mm/year in the Kara Sea, while the annual average precipitation in the East Siberian Sea and the Laptev Sea is 48-303 mm/year and 53-177 mm/year respectively. The largest monthly average precipitation is concentrated in September in the NEP. The correlation analysis of the precipitation and SIC shows that the correlation coefficient between precipitation and SIC is -0.792 in the NEP in the recent decade, and there is a 15-day delay between precipitation and sea ice. Therefore, through the analysis of precipitation data in these areas, it is found that precipitation is related to the navigable capacity of the NEP and has a great reference value for understanding and predicting precipitation.